Determinants of Financial Performance on Profit Growth with Company Size as a Moderating Variable (Case Study of a Food and Beverage Sub-Sector Company) - Achmad Ludvy; Rizka Wahyuni Amelia; Lina Nofiana (Transpublika Publisher, 2026)
Employing a quantitative framework and panel data regression, this study explores how profit growth is affected by the Quick Ratio, Debt to Equity Ratio, and Net Profit Margin, while company size acts as a moderating variable. The research is confined to food and beverage subsector entities listed on the Indonesia Stock Exchange across the 2019-2024 timeframe. A balanced panel of 102 observations, drawn from a sample of 17 companies, underpins the analysis over the six complete fiscal years. Based on the results of the Chow and Hausman tests, the Fixed Effect Model (FEM) is identified as the most appropriate framework. Moderated Regression Analysis (MRA) is used to test for moderation effects. Partial coefficient estimates indicate a negative and significant relationship between the Debt to Equity Ratio and profit growth. In contrast, the Net Profit Margin exhibits a positive and significant relationship with profit growth. The Quick Ratio, however, does not significantly influence profit growth. Findings from the moderation test suggest that company size cannot moderate the effects of QR, DER, or NPM on profit growth. With an R² value of 42.68 percent, the independent variables in this study explain 42.68 percent of the variability in profit growth, while other factors not included in the model account for the remaining 57.32 percent. The findings provide practical implications for managers by emphasizing that improving profitability and maintaining an optimal capital structure are more important for enhancing profit growth than simply increasing company size.